ANALISIS PEMULIHAN CITRA MELALUI PRESS RELEASE PASCA PEMADAMAN LISTRIK DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI MELALUI PENDEKATAN IMAGE RESTORATION - Ni Putu Denisa Indrayanti; Gusti Agung Alit Suryawati (Program Studi Komunikasi dan Penyiaran Islam, 2026)
The power outage that occurred at I Gusti Ngurah Rai International Airport caused operational disruptions and had the potential to affect the institution’s image as a provider of air transportation services. This study aims to analyze the image restoration strategies implemented by I Gusti Ngurah Rai International Airport through press releases following the incident, using William L. Benoit’s Image Restoration Theory as the analytical framework. This research employs a descriptive qualitative method with content analysis techniques applied to official press releases published on the official website of I Gusti Ngurah Rai International Airport. The findings indicate that the airport implemented a combination of image restoration strategies, including mortification, corrective action, and bolstering. The absence of denial and evasion of responsibility strategies suggests that the airport adopted a transparent and non-defensive communication approach. This study concludes that official press releases play a crucial role as crisis communication instruments in efforts to restore organizational image following public service crises. These findings reinforce the relevance of Benoit’s Image Restoration Theory in analyzing crisis communication strategies within the air transportation sector.